Ameliorative effect of Silk Fibroin against 5-Fluorouracil (5-FU)-induced gastrointestinal damage in rats - Şehirli, Ahmet Özer; Aykaç, Aslı; Özkayalar, Hanife; Savtekin, Gökçe; Sayıner, Serkan; Sayıner, Serkan (Bangladesh Journal of Medical Science, 2023)
Objective: 5-Fluorouracil (5-FU), a widely administered anti-cancer drug, causes gastrointestinal damage through various mechanisms. This study aimed to investigate the ameliorative effect of silk fibroin (SF), which has anti-inflammatory and antioxidant properties, against 5 FU-induced gastrointestinal damage. Materials and methods: Wistar albino rats were divided into 3 groups; Control group, 5- FU group (30mg/kg/day on days 0, 2, 4), and 5-FU+SF (30 mg/kg/day 5-FU on days 0, 2, 4 + 600 mg/kg/day SF for 14 days). At the end of the experiment, stomach and intestinal tissue samples were collected and immunohistochemically iNOS, caspase-3, CD4+ and CD8+ were measured. Besides, structural damage was assessed with hematoxylin-eosin and caspase-3 and 9 activities were evaluated using western blot analysis. Results and Discussion: It was determined that iNOS, caspase-3, caspase-9 activities, CD4+ and CD8+ levels and structural damage significantly increased in both stomach and intestinal tissues. Furthermore, elevated markers were regressed almost to control levels in SF administrated group. Conclusion: SF may have an ameliorative effect, thus reducing the gastrointestinal damage caused by 5 FU. More clinical and scientific research should be conducted as the silk fibroin may be a suitable candidate against the adverse effects of chemotherapeuic agents. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 907-915